PENGARUH METODE MEANINGFULL LEARNING TERHADAP KETERAMPILAN KOGNITIF SISWA SEKOLAH DASAR - Nazulfah Widiana, Indah; Rachmadtullah, Reza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this research is to find out whether the Meaningfull Learning method has an influence on the cognitive skills of elementary school students. This research uses quantitative methods with a quasi-experiment and post-test only control group design. Participants in this research involved fifth grade elementary school students. Consisting of 2 classes, namely class VA (control) using the conventional learning model and class VB (experiment) using the Meaningfull Learning method. The data collection method in this research uses a test study. Based on the results of research conducted and processed using SPSS 21, it is known that the t-count is greater than the t-table. Due to the fact that the average scores were found in the posttest, the VA and VB class scores were based on the control and experimental groups, respectively. From the data analysis, it can be interpreted that there is a positive and significant influence of the Meaningfull Learning Method on the Cognitive Skills of Elementary School Students.